PENERAPAN MEDIA INTERACTIVE WALL WRITING UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA AUTIS DI SLB NEGERI 1 MAKASSAR - Grace Ellen Risakotta; Tatiana Meidina; Syamsuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the writing ability of an autistic student through the implementation of interactive wall writing media at SLB Negeri 1 Makassar. The study aimed to determine the student's writing ability before and after the implementation of interactive wall writing media and to describe the improvement achieved. This study used a quantitative approach with descriptive research. The subject was one first-grade autistic student at SLB Negeri 1 Makassar. Data were collected using a performance test administered before and after the implementation of the media. Data analysis was conducted descriptively by comparing the pretest and posttest scores based on the predetermined assessment criteria. The results showed that before the implementation of interactive wall writing media, the student's writing ability was in the failed category with a score of 0. After the implementation through a structured learning process, the student obtained a score of 9 out of a maximum score of 12, equivalent to a value of 75 and categorized as good. The improvement was also observed in the student's ability to hold writing tools, follow writing patterns, maintain attention, and complete writing activities with reduced assistance. Thus, the implementation of interactive wall writing media improved the writing ability of the autistic student at SLB Negeri 1 Makassar.